2021
DOI: 10.1097/01.naj.0000794104.21262.86
|View full text |Cite
|
Sign up to set email alerts
|

CE: Hypertensive Emergencies: A Review

Abstract: While acute blood pressure elevations are commonly seen in the ED, not all require emergency treatment. True hypertensive emergencies are characterized by a rapid elevation in blood pressure to a level above 180/120 mmHg and are associated with acute target organ damage, which requires immediate hospitalization for close hemodynamic monitoring and IV pharmacotherapy. Recognizing the clinical signs and symptoms of hypertensive emergency, which may vary widely depending on the target organ involved, is critical.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(64 citation statements)
references
References 53 publications
0
63
1
Order By: Relevance
“…In that sense, the prevalence of CH differs when calculated for the group without a diagnosis and with a previous diagnosis of HTA. Our result in patients without a history of HTA is much lower than that found in an Italian study that reported a prevalence of CH of 23% (13) but in an emergency room, and obviously much lower than in those with CH who developed target organ damage, where more than half did not have a previous diagnosis of HTA (22). However, it has been described that the highest proportion of hypertensive crises occurs in those with a history of HTA (23).…”
Section: Comparison With Previous Studiescontrasting
confidence: 86%
See 1 more Smart Citation
“…In that sense, the prevalence of CH differs when calculated for the group without a diagnosis and with a previous diagnosis of HTA. Our result in patients without a history of HTA is much lower than that found in an Italian study that reported a prevalence of CH of 23% (13) but in an emergency room, and obviously much lower than in those with CH who developed target organ damage, where more than half did not have a previous diagnosis of HTA (22). However, it has been described that the highest proportion of hypertensive crises occurs in those with a history of HTA (23).…”
Section: Comparison With Previous Studiescontrasting
confidence: 86%
“…A Canadian study conducted in an urban center, using a mobile clinic, evaluated a total of 1 097 individuals with a wider age range (16-92 years), and the result was a prevalence of 2% of CH in patients without symptoms (18), exceeding what was found in the present study. However, the prevalence of hypertension found in this report was 50%, highlighting the fact of some type of selection bias, i.e., those who believed they had HTA were evaluated in the medical clinic, which leads to other associated problems such as poor adherence to treatment (19).…”
Section: Comparison With Previous Studiesmentioning
confidence: 63%
“…Hypertensive crises are also caused in part by a failure of the autoregulatory mechanisms at the level of the vascular bed. Normally, an increase in blood pressure triggers an inherent vascular, myogenic response where small arteries constrict to limit sudden increases in blood flow to the capillary endothelium 1. Endothelial damage results from mechanical injury of high blood pressure that damages the endothelial beds 1,7.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Hypertensive urgency is characterized by high blood pressure, not defined at a specific numerical value 3. Very high blood pressures with an increase in the risk factors that may lead to EOD would qualify as hypertensive urgency, despite no evidence of new or worsened EOD at presentation 1,3. Although 18% to 25% of emergency visits had severely high blood pressure, a true hypertensive emergency is rarer, accounting for just 0.2% to 0.3% of emergency department visits 3,4.…”
mentioning
confidence: 99%
“…The distinction between these two clinical entities is essential because of the major differences in management and treatment [ 15 ]. Briefly, patients presenting with HE should receive immediate care, ideally by pharmacological and nonpharmacological interventions for lowering BP levels, especially through the administration of intravenous drugs and specific treatment protocols for the associated clinical conditions including acute coronary syndrome (ACS), acute heart failure with pulmonary oedema, acute aortic syndrome, hypertensive encephalopathy, ischemic or hemorrhagic stroke, pre-eclampsia/eclampsia [ 16 ].…”
Section: Definition and Epidemiology—setting The Stagementioning
confidence: 99%